Towards Efficient Construction Projects: Addressing Team Coordination and Risk Management in Jordan: Higher Model Imperial Study - Alshamayleh, Hareth Zuhair; Abu Raje, Hasan Mohd Talat Ahmad; Amlus, Mohammad Harith Bin; Bataineh, Mohammad Jamal (Journal of Ecohumanism, 2024)
The Jordanian construction industry is plagued by critical challenges such as poor team coordination and inadequate risk management, leading to project delays, increased costs, and compromised quality. This study focuses on identifying these issues and proposing strategic interventions to enhance project outcomes. A survey of 204 engineering managers was conducted, and data were analyzed using Partial Least Squares (PLS) to assess the impact of team coordination and risk management practices on project performance. Findings reveal that miscommunication, unclear role definitions, and lack of centralized coordination significantly hinder project success. By applying the Resource-Based View (RBV) theory, this research underscores the importance of strategic management of internal resources, particularly team coordination, to achieve competitive advantage and improved project performance. The study recommends policy adjustments to facilitate the hiring of skilled expatriate labor, investment in continuous professional development, and the adoption of modern engineering management practices, including advanced project management tools like BIM and mobile apps. Additionally, implementing systematic risk management practices tailored to the Jordanian context is crucial for mitigating potential risks and ensuring project stability. These strategic interventions are expected to enhance project performance, reduce costs, and ensure timely completion, contributing to the sustainable growth and development of Jordan's construction industry. This research provides valuable insights and a comprehensive roadmap for industry stakeholders to address current challenges and improve overall project outcomes.